MODEL BIMBINGAN KESEHATAN MENTAL UNTUK PARA SANTRI PONDOK PESANTREN SYAFI’IYAH CISAMBENG MAJALENGKA - Yedi Supriadi (Oasis : Jurnal Ilmiah Kajian Islam, 2017)
The goal  of the research  are  to describe  the development of the mental health  for young students at the boarding  school in the islamic school of Syafi'iyyah in Cisambeng city of  Palasah-Majalengka  regency.  Development  of  mental  health  in  question  is  with  the planting of character and morals and a healthy mental approach to the students through some methode is called  “shuhbah” (friendship)  for the  purpose  of mental  development can  be achieved easily, accurately,  effectively and efficiently. The method of the research  are using descriptive   method   with  collecting   some   information,   by  techniques   gained   through observation,  interviews, questionnaires  and documentation  study. Data  retrieval  is derived from respondents who are seen mental health problems with a purposive sampling technique that aims to find out what the problem occurs in teenagers  these students then how after he followed the  guidance  of mental  health  at  boarding  Syafi'iyyah Cisambeng  approach  by “shuhbah” (friendship). Islamic conseling emphasizes spiritual  solutions based on love and fear of Allah and the duty of fulfil our responsibility as the servants of Allah on this earth.The results of the research  illustrate  that the application  of mental health counseling with shuhbah (friendship) perceived benefit to the students who participated  in mental health counseling because  after being interviewed and completed questionnaires  the students who have experienced problems of mental disorders  (misconduct) after obtaining calculated  the mean category average high.Based on the recognition  of the students,  they are  feel much better  after  attending mental health training  activities in Pondok Pesantren  Syafi'iyyah Cisambeng guided by Mas Nawawi (Ustd.Muhamad Nawawi Fathulloh, M.Pd.I). Thus the results of this study presented a picture of the actual conditions in the field as the information and report the study authors. Keywords: Model Guidance, Mental Health,  and Pupils